Method for preparing super-hydrophobic flame-retardant flexible material from water-dispersed nanocellulose compound
By introducing nanoscale silica, methyl trimethoxysilane and polyvinyl alcohol into the water-dispersible plant nanocellulose composite, superhydrophobic flame retardant flexible materials are prepared, which solves the complexity and resource waste of water removal in the prior art, and achieves efficient and environmentally friendly oil-water separation and flame retardant effects.
Patent Information
- Application Number
- CN202510188152.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-20
AI Technical Summary
The prior art has problems with the use of harmful or expensive precursors, complex processes and equipment in removing organic pollutants in water bodies, and is seriously wasteful of resources and environmental pollution.
By using water as a dispersible medium, a water-dispersible plant nanocellulose composite is prepared, combining nanoscale silica, methyltrimethoxysilane and polyvinyl alcohol to form a superhydrophobic flame retardant flexible material. The material is prepared by freeze-drying to form a three-dimensional superporous structure, achieving flame retardant and efficient oil-water separation.
It achieves high elasticity, high oil absorption, reusability, fire resistance and degradability, reduces production costs, avoids air pollution and fire hazards caused by volatility of organic solvents, broadens the application fields and improves safety and circulation stability.
Smart Images

Figure CN119661897A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrophobic flame retardant materials, in particular to a method for preparing a super hydrophobic flame retardant flexible material with a water-dispersed nano cellulose composite. Background Art
[0002] Organic pollutants have the characteristics of high toxicity, low solubility, and high persistence, which cause serious harm to aquatic organisms and human health. With the advancement of global industrialization, a large amount of organic pollutants are discharged into water bodies. Therefore, there is an urgent need to develop materials and methods that can effectively remove organic pollutants from water bodies. However, the preparation of most materials usually involves harmful or expensive precursors, complex processes and equipment, and there is an urgent need to find a green, environmentally friendly and economical way to solve this problem. Cellulose is the most abundant natural polymer material in nature. It has the advantages of being completely biodegradable, non-toxic, pollution-free, easy to modify, and good biocompatibility. However, hundreds of millions of tons of cellulose-rich biomass resources are directly crushed, buried or burned every year, causing serious waste of resources and environmental pollution. Corn stalks produced in agricultural production in my country are abundant, and the cellulose content in corn stalks is as high as 32%. Therefore, how to turn waste into treasure and use corn and other crop straws efficiently and at low cost has become a research and development hotspot in the field of biomass resource utilization in countries around the world.
[0003] Silicon dioxide (SiO2) is an inorganic compound that is ubiquitous in nature and is widely used in industry mainly for its stable physical and chemical properties. In addition, it also has the advantages of high fire resistance, high temperature resistance, insulation, corrosion resistance, piezoelectricity, resonance and optical properties. In the present invention, nano-scale SiO2 is synthesized using ethyl orthosilicate as a silicon source and ammonia water as a catalyst. Nanocellulose (CNF) has the advantages of wide source, renewable, rich in hydroxyl groups, stable structure, biodegradability, and strong biocompatibility. In the present invention, CNF is obtained from agricultural and forestry wastes by hot solvent pretreatment, low eutectic solvent separation, sodium chlorite solution bleaching, and high-intensity ultrasonic treatment. Methyltrimethoxysilane (MTMS) is an organic silicon compound with excellent heat resistance, chemical stability, adhesion, hydrophobicity, and surface activity. In the water-dispersible plant nanocellulose composite of the present invention, a large amount of nano-SiO2 is wrapped on the surface of CNF to form a covering layer, which will become a barrier between the subsequent condensed phase and the flame to isolate oxygen and achieve a flame retardant effect; MTMS can form a strong chemical bond with the hydroxyl groups on the surface of CNF and SiO2, enhance its adhesion and complete hydrophobic modification; the addition of polyvinyl alcohol (PVA) will improve the composite and dispersibility of the above materials in water, greatly enhancing the flexibility and mechanical stability of the materials; the three-dimensional ultra-porous structure formed by the super-hydrophobic flame-retardant flexible material prepared by freeze-drying will diffuse the heat and make it unable to focus, reduce the heat fed back to the material, thereby inhibiting its own thermal cracking and combustion reactions, and achieving the purpose of thorough combustion to remove internal pollutants and continue recycling.
[0004] Most hydrophobic materials are organic dispersion systems before molding, or are prepared by further treating hydrophilic materials with hydrophobic modified solutions (generally in organic solvents). The present invention uses water instead of organic solvents as a dispersion medium to obtain a water-dispersible plant nanocellulose composite, and then prepares a super-hydrophobic flame-retardant flexible material with rich pores. The material has the characteristics of high elasticity, high porosity, low density, high oil absorption, high throughput, reusability, fire resistance, and degradability. The preparation process is green and pollution-free, and better avoids safety hazards such as air pollution and fire caused by the volatilization of organic solvents. Compared with organic solvents, water resources are more abundant and easy to obtain, and in the preparation process of super-hydrophobic flame-retardant flexible materials, resources and costs can be greatly saved. Accordingly, the present invention proposes a method for preparing a super-hydrophobic flame-retardant flexible material using a water-dispersible plant nanocellulose composite and its application. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a super-hydrophobic flame-retardant flexible material from a water-dispersible nanocellulose composite. The material preparation process is green and pollution-free, and the prepared flexible material has the characteristics of high elasticity, high oil absorption, reusability, fire resistance, degradability, etc., and can be applied to a variety of fields.
[0006] To achieve the above object, the present invention provides a method for preparing a super-hydrophobic flame-retardant flexible material by using a water-dispersible nanocellulose composite, comprising the following steps: Step 1, nanocellulose CNF suspension; Step 2, synthesizing silicon dioxide nanoparticles SiO2NPS; Step 3, preparing a precursor suspension CSM: mixing SiO2 nanoparticles, methyltrimethoxysilane MTMS and nanocellulose suspension in proportion, reacting to obtain a precursor suspension CSM; Step 4, preparing a polyvinyl alcohol (PVA) solution: adding PVA solid to deionized water, heating and stirring at 85° C. until completely dissolved, to obtain a PVA solution; Step 5, preparing a water-dispersible plant nanocellulose composite CSM-PVA mixed solution: blending the materials prepared in step 3 and step 4 to prepare a CSM-PVA mixed solution, and freezing the mixture; Step 6, freeze-drying the frozen material, and then placing it in an oven for heat treatment to obtain a super hydrophobic flame retardant flexible material.
[0007] Furthermore, the preparation method of the nanocellulose CNF suspension in step 1 is: the straw raw material is prepared by hot solvent pretreatment, low eutectic solvent separation, sodium chlorite solution bleaching, and high-intensity ultrasonic treatment; the concentration of the nanocellulose CNF suspension is 0.95~1.05 wt%.
[0008] Furthermore, the specific operation of step 2 is: mixing anhydrous ethanol, deionized water and ammonia water, and preparing liquid A after ultrasonic treatment; mixing tetraethyl orthosilicate TEOS and anhydrous ethanol, and preparing liquid B after ultrasonic treatment; at 45°C, slowly pouring liquid A into liquid B twice in a ratio of 3 / 4 and 1 / 4, with an interval of 1 hour. After the reaction is completed, centrifuge, rinse with deionized water and ethanol, and dry to obtain SiO2 nanoparticles.
[0009] Furthermore, in step 3, the mass ratio of nanocellulose suspension: SiO2 nanoparticles: methyltrimethoxysilane is 3.70~3.80 g: 0.025~0.031 g: 0.9~1.1 g.
[0010] Furthermore, the concentration of the PVA solution in step 4 is 9.5-10.5 mg / mL.
[0011] Furthermore, the specific operation of step 5 is: the precursor suspension CSM and the PVA solution are blended in proportion, and mechanically stirred at a speed of 1950-2050 rpm for 4-6 min to obtain a water-dispersible plant nanocellulose composite CSM-PVA mixed solution.
[0012] Furthermore, the dosage ratio of the precursor suspension CSM and the PVA solution is (1-5): (1-5).
[0013] The present invention also provides a super-hydrophobic flame-retardant flexible material prepared by the method.
[0014] The present invention also provides application of the super-hydrophobic flame-retardant flexible material in separation of oily wastewater and emulsion.
[0015] The present invention also provides the use of the super-hydrophobic flame-retardant flexible material in flame retardancy, circulating oil adsorption, and combustion desorption.
[0016] The advantages and positive effects of the method for preparing super-hydrophobic flame-retardant flexible materials using the water-dispersible nanocellulose composite of the present invention are: 1. The present invention uses water as a dispersion medium, and the preparation process of the super hydrophobic flame retardant flexible material is non-toxic, environmentally friendly, green and pollution-free, and better avoids the potential safety hazards such as air pollution and fire caused by the volatilization of organic solvents. Compared with organic solvents, water resources are more abundant and easy to obtain, which can greatly save the preparation cost of super hydrophobic flame retardant flexible materials.
[0017] 2. After the silanol of SiO2 in the present invention is combined with the hydroxyl of cellulose, a large amount of nano-scale SiO2 will wrap around the surface of CNF to form a covering layer, which becomes a barrier between the subsequent condensed phase and the flame to isolate oxygen and achieve a flame retardant effect. At the same time, the three-dimensional ultra-porous structure of the super-hydrophobic flame-retardant flexible material will diffuse the heat and make it impossible to focus, reducing the heat fed back to the material, thereby inhibiting its own thermal cracking and combustion reactions, achieving the purpose of thorough combustion to remove internal pollutants and continue to recycle.
[0018] 3. In the present invention, MTMS forms a strong chemical bond with the hydroxyl groups on the surface of CNF and SiO2, enhancing their adhesion and completing hydrophobic modification; the addition of polyvinyl alcohol (PVA) improves the composite and dispersibility of the above materials in water, and freeze-drying and further heat treatment give the material excellent superhydrophobicity, flame retardancy, flexibility and mechanical stability.
[0019] 4. The super hydrophobic flame retardant flexible material of the present invention has extremely high specific surface area and porosity, and the adsorption capacity of the super hydrophobic flame retardant flexible material is very considerable. Therefore, the material is very suitable for purification of oil-containing water bodies, and has the advantages of stable structure, low cost, environmental friendliness, and convenient carrying.
[0020] 5. The three-dimensional super-porous structure of the super-hydrophobic flame-retardant flexible material in the present invention is conducive to the rapid diffusion and flow of liquid molecules, and its continuous channels also make its adsorption process more efficient; in the field of oil spill wastewater treatment, it can selectively and quickly absorb, store and transport oil, greatly improving the material's purification ability and separation efficiency for oily wastewater.
[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a flow chart for preparing the CSM-PVA super-hydrophobic flame-retardant flexible material in an embodiment of the present invention; Figure 2 is the proportion of each component of the CSM-PVA6 water-dispersible plant nanocellulose composite in the embodiment of the present invention; Figure 3 The contact angle images of the surfaces of 9 CSM-PVA super-hydrophobic flame-retardant flexible materials prepared by the present invention in air, wherein (a) is the water contact angle, and (b) is the oil contact angle; Figure 4 A in Figure 3 A is a bar graph of the surface contact angles of 9 CSM-PVA super-hydrophobic flame-retardant flexible materials, and B is a graph showing the change of water contact angle of CSM-PVA6 super-hydrophobic flame-retardant flexible material in air within 6 minutes; Figure 5 Scanning electron microscope (SEM) images of CSM-PVA6 at different magnifications, where (a) is 100 times magnification, (b) is 500 times magnification, (c) is 5000 times magnification, and (d) is 30000 times magnification; Figure 6 The CSM-PVA6 super-hydrophobic flame-retardant flexible material is placed in the oil and water of the mixed liquid, where (a) is in the oil, (b) is in the water, and (c) is the enlarged view of point ① in (b); Figure 7 (a) is the effect of oil droplets and water droplets on the surface of unheat-treated CSM-PVA material, (b) is the effect of oil droplets and water droplets on the surface of heat-treated CMS-PVA6 super-hydrophobic flame-retardant flexible material, (c) is the effect of oil droplets and water droplets on the inside of heat-treated CMS-PVA6 super-hydrophobic flame-retardant flexible material, red is oil droplets, blue is water droplets; Figure 8 This is a manual compression rebound performance test of the CMS-PVA6 super-hydrophobic flame-retardant flexible material prepared in an embodiment of the present invention, wherein (a) is before compression, (b) is during compression, and (c) is after compression; Fig. 9 The weight is placed on the CMS-PVA6 super hydrophobic flame retardant flexible material to test the compression rebound performance, where (a) is before the test and (b) is after the test; Fig.10 The CMS-PVA6 super hydrophobic flame retardant flexible material prepared in the embodiment of the present invention is subjected to 30 cycles of compression test at 80% strain; Fig.11 This is the test of CMS-PVA6 super hydrophobic flame retardant flexible material by universal testing machine, where (a) is before the test; (b) is after the test; Fig.12 This is the test of CMS-PVA6 super hydrophobic flame retardant flexible material in a wet state by a universal testing machine, where (a) is before the test; (b) is after the test; Fig.13 This is a photo of water rolling down the surface of CMS-PVA6 superhydrophobic flame-retardant flexible material under oil; Fig.14 The CMS-PVA6 super hydrophobic flame retardant flexible material prepared in the embodiment of the present invention adsorbs n-hexane and chloroform in water, wherein (a) is n-hexane, ① is before adsorption, and ② is after adsorption; (b) is chloroform, ③ is before adsorption, and ④ is after adsorption; Fig.15 The peristaltic pump is used to drive the CSM-PVA6 super-hydrophobic flame-retardant flexible material to separate oil and water, where (a) is n-butane / water, ① is before separation, ② is after separation; (b) is chloroform / water, ③ is before separation, ④ is after separation; (c) is dichloromethane / water, ⑤ is before separation, ⑥ is after separation; (d) is dichloroethane / water, ⑦ is before separation, ⑧ is after separation; Fig.16 Gravity-driven filtration device for oil-water separation, where (a) is the oil-water separation device, (b) is the separation flux and separation efficiency of CSM-PVA6 super-hydrophobic flame-retardant flexible material for n-hexane / water, dichloroethane / water, dichloromethane / water and chloroform / water mixtures, and (c) is the oil-water separation model diagram; Fig.17 The separation flux and efficiency of the CSM-PVA6 super hydrophobic flame retardant flexible material prepared in the present invention after 12 times of chloroform / water mixed liquid tests; Fig.18 The adsorption capacity of various oils (chloroform, ethylene dichloride, dichloromethane and n-hexane) by the super hydrophobic flame retardant flexible materials CSM-PVA5, CSM-PVA6 and CSM-PVA7 prepared in the present invention; Fig.19 This is a test effect diagram of a gravity-driven filtering device in an embodiment of the present invention; Fig. 20 The effect diagram of the gravity-driven filtration device for oil-in-water emulsion separation in the embodiment of the present invention, wherein (a) is dichloromethane, ① is the effect before separation, ② is the effect after separation; (b) is chloroform, ③ is the effect before separation, ④ is the effect after separation; (c) is dichloroethane, ⑤ is the effect before separation, ⑥ is the effect after separation; (d) is n-hexane, ⑦ is the effect before separation, ⑧ is the effect after separation; Fig.21The separation flux and efficiency of the CSM-PVA6 super-hydrophobic flame-retardant flexible material prepared by the present invention for four oil-in-water emulsions (dichloroethane / water, dichloromethane / water, chloroform / water and n-hexane / water); Fig. 22 The separation flux and efficiency of the CSM-PVA6 super hydrophobic flame retardant flexible material prepared by the present invention after 10 times of dichloroethane water emulsion test; Fig.23 The flame retardant performance test of the CSM-PVA6 super hydrophobic flame retardant flexible material prepared by the present invention in air, (a) is before combustion, (b) is after 4s of combustion, (c) is after 6s of combustion, and (d) is after 8s of combustion; Fig.24 (a) is the flame retardant performance test of the unextruded CSM-PVA6 super hydrophobic flame retardant flexible material in the air under the saturated state of n-hexane adsorption, ① is before combustion, ② is after combustion; (b) is the flame retardant performance test of the extruded CSM-PVA6 super hydrophobic flame retardant flexible material in the air under the saturated state of n-hexane adsorption, ③ is before combustion, ④ is after combustion; Fig.25 The flame retardant performance test of CSM-PVA6 super-hydrophobic flame retardant flexible material in a vial after oil absorption, where (a) is before combustion, (b) is after 60s of combustion, (c) is after 120s of combustion, and (d) is after 160s of combustion; Fig.26 The adsorption-combustion-desorption cycle performance test of the CSM-PVA6 super-hydrophobic flame-retardant flexible material prepared by the present invention; Fig. 27 The CSM-PVA6 super hydrophobic flame retardant flexible material prepared by the present invention is compared before and after 10 adsorption-combustion desorption cycle tests, wherein (a) is before the test and (b) is after the test; Fig.28 The contact angles of the CSM-PVA6 super-hydrophobic flame-retardant flexible material prepared in the present invention to liquids of different pH values. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0024] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0025] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. The experimental methods without specific conditions in the following examples are usually measured in accordance with national standards. The experimental instruments, equipment and reagents without source indication in the following examples are all commercially available raw materials.
[0026] Unless otherwise defined or described, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein can be applied to the method of the present invention. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0027] Example 1 A method for preparing a nanocellulose suspension comprises the following steps: (1) Thermal solvent treatment: 5 g corn straw powder, wheat straw powder, poplar wood powder or pine wood powder was mixed with 30 mL anhydrous ethanol, 15 mL deionized water and 190 μL concentrated sulfuric acid, stirred evenly and placed in a reactor for heat treatment at 185 °C for 90 min. After the reaction was complete, the reactor was taken out and continuously rinsed with a small stream of water until it reached room temperature. After cooling, the reactants in the reactor were taken out and rinsed with 65% ethanol solution until neutral. The reactants were filtered with a funnel, and the ethanol was washed with deionized water. The solid powder of corn straw, wheat straw, poplar wood or pine wood was obtained after drying in an oven at 60 °C for 2 h.
[0028] (2) Preparation of deep eutectic solvent (DES): Choline chloride and oxalic acid were mixed in a mass ratio of 2.1:1.9 and heated at 80 °C for 1 h until a transparent solution was obtained to obtain a deep eutectic solvent (DES).
[0029] (3) High-temperature oil bath treatment: The corn stalk powder treated in step (1) and the low eutectic solvent in step (2) are mixed in a mass ratio of 1:20, stirred evenly, and placed in an oil bath pot. The mixture is reacted at 110 °C for 8 h and then cooled to room temperature. The residual solid is placed in a funnel and filtered, and then rinsed with deionized water and a small amount of anhydrous ethanol until the filtrate is completely transparent and clean.
[0030] (4) Sodium chlorite bleaching treatment: 3 g of the residual solid after treatment in step (3) was mixed with 100 mL of 1.5-2 wt% sodium chlorite solution, and the pH of the solution was adjusted to 3 using glacial acetic acid (300 μL). The solution was placed in a water bath at a constant temperature of 80 °C and magnetically stirred for 1 h. Finally, the residual solid after bleaching was placed in a funnel for suction filtration, and then rinsed with deionized water until the filtrate was completely transparent and clean, thereby obtaining a high-purity cellulose solid powder.
[0031] (5) High-intensity ultrasonic treatment: 1 g of the high-purity cellulose solid powder obtained in step (4) was uniformly dispersed in 99 mL of deionized water, and then subjected to high-intensity ultrasonic treatment in an ultrasonic cell disruptor (900 W) for 30 min to obtain a 1 wt% nanocellulose suspension.
[0032] Example 2 Another method for preparing a nanocellulose suspension comprises the following steps: (1) Sodium chlorite bleaching treatment: Take 5 g corn straw, wheat straw, poplar wood powder or pine wood powder, mix it with 150 mL sodium chlorite solution (1.5 wt%), use glacial acetic acid (300 μL) to adjust the pH of the above solution to 3, and keep stirring for 6 h at a constant temperature of 80 °C in a water bath. During the reaction, add 300 μL glacial acetic acid and 0.2 g sodium chlorite solid to the above mixture every 1 h. Finally, the residual solid after bleaching is placed in a funnel for suction filtration, and then rinsed with deionized water until the filtrate is completely transparent and clean, to obtain bleached corn straw, wheat straw, poplar wood powder or pine wood powder solid powder.
[0033] (2) Thermal solvent treatment: The bleached corn straw powder, wheat straw powder, poplar wood powder or pine wood powder in step (1) is mixed with 45 mL of anhydrous ethanol, 15 mL of deionized water and 190 μL of concentrated sulfuric acid, stirred evenly and placed in a reactor for thermal treatment at 185°C for 90 min. After the reaction is complete, the reactor is taken out and continuously rinsed with a small stream of water until it reaches room temperature. After cooling, the reactants in the reactor are taken out and rinsed with a 65% ethanol solution until it is neutral. The reactants are filtered with a funnel, and the ethanol is washed off with deionized water. The solid powder of the treated corn straw, wheat straw, poplar wood or pine wood is obtained after drying in an oven at 60°C for 2 h.
[0034] (3) Further bleaching treatment: After 10 mL of hydrogen peroxide (H2O2) and 45 mL of NaOH solution (1 wt%) were mixed evenly, the residual solid in step (2) was added, and then stirred and reacted in a water bath at a constant temperature of 50 °C for 90 min to complete the further removal of lignin and hemicellulose. Then, the residual solid was placed in a funnel for suction filtration and then rinsed with deionized water until the filtrate was completely transparent and clean, thereby obtaining a high-purity cellulose solid powder.
[0035] (4) High-intensity ultrasonic treatment: 1 g of the high-purity cellulose solid powder in step (4) was uniformly dispersed in 99 mL of deionized water, and then subjected to high-intensity ultrasonic treatment in an ultrasonic cell disruptor (900 W) for 30 min to obtain a 1 wt% nanocellulose suspension.
[0036] Example 3 A method for preparing a super-hydrophobic flame-retardant flexible material from a water-dispersible plant nanocellulose composite comprises the following steps: S1. Prepare a nanocellulose suspension, as in Example 1 and Example 2.
[0037] S2. Synthesize silica nanoparticles (SiO2NPS).
[0038] (1) Preparation of Solution A: Mix 4 mL of deionized water, 12 mL of aqueous ammonia, and 150 mL of anhydrous ethanol and treat with an ultrasonic cleaner for 15 min to obtain Solution A.
[0039] (2) Preparation of Solution B: Mix 6 mL of TEOS with 50 mL of anhydrous ethanol and ultrasonically treat the mixture for 25 min to obtain Solution B.
[0040] (3) Preparation of SiO2NPS: Under magnetic stirring at a constant temperature of 45°C in a water bath, ¾ of solution A was slowly poured into solution B and reacted for 1 hour until the solution gradually became turbid. Then, the remaining solution A was poured into the above solution and continued to react for 1 hour. After the reaction was completed, the SiO2 nanoparticles were obtained by centrifugation (speed 10300 r / min, 15 min), rinsing with deionized water and ethanol, repeated three times and dried (60°C, 6 h).
[0041] S3. Prepare precursor suspension CSM.
[0042] (1) Take 45 mL of CNF suspension (1 wt%) and mix it evenly with 0.34 g of SiO2NPS.
[0043] (2) Add 5 mL of CNF suspension and 6 mL of MTMS to the mixed solution in step (1), and stir continuously for 1 h at a constant temperature of 80 °C in a water bath to obtain a precursor suspension CSM.
[0044] S4. Prepare polyvinyl alcohol (PVA) solution.
[0045] 1 g of PVA solid was added into 99 mL of deionized water and stirred continuously for 1 h in a water bath at a constant temperature of 80 °C to prepare a 1 wt% PVA solution.
[0046] S5. Prepare water-dispersible plant nanocellulose composite (CSM-PVA mixed solution).
[0047] The precursor suspension CSM in step S3 and the PVA solution in step S4 are mixed and homogenized in accordance with the steps to prepare water-dispersible plant nanocellulose composites (CSM-PVA mixed solutions) with different proportions, and then the composites are transferred into a mold for freezing treatment.
[0048] S6. Preparation of superhydrophobic flame-retardant flexible materials using water-dispersible plant nanocellulose composites.
[0049] The composite in step S5 was freeze-dried for 48 h and then placed in an oven at a constant temperature of 100 °C for 3 h to obtain a biomass flame-retardant flexible material CSM-PVA with superhydrophobic and superoleophilic properties. The overall preparation process is shown in the following figure: Figure 1 shown.
[0050] Different biomass flame retardant flexible materials CSM-PVA were prepared by adjusting the ratio of the precursor suspension CSM and the PVA solution. The preparation method was the same as that in Example 3, except for the ratio of the precursor suspension CSM and the PVA solution.
[0051] The prepared biomass flame retardant flexible material CSM-PVA is shown in Table 1.
[0052] Table 1 Biomass flame retardant flexible material CSM-PVA ;
[0053] The proportions of the components of biomass flame retardant flexible material CSM-PVA6 are as follows: Figure 2 shown.
[0054] Performance Testing 1. Performance test of the prepared super hydrophobic flame retardant flexible material: (1) Optimization of special wetting properties and structural stability of super hydrophobic flame retardant flexible material CSM-PVA: ① The prepared CSM-PVA super-hydrophobic flame-retardant flexible material was heat-treated, and then the water contact angle and oil contact angle on its surface and inside were measured using a contact angle meter, proving the excellent super-hydrophobicity and super-oleophilicity of the CSM-PVA super-hydrophobic flame-retardant flexible material.
[0055] Figure 2 This is a fan-shaped chart of the proportion of each component of the super hydrophobic flame retardant flexible material CSM-PVA6. Among them, CNF suspension accounts for 37.41%; SiO2NPS accounts for 0.28%; MTMS accounts for 2.44%; PVA solution accounts for 59.86%. The super hydrophobic flame retardant flexible material CSM-PVA6 has a diameter of 10.24 mm, a height of 14.91 mm, a weight of 0.226 g, and a density of 0.046 g / cm -3 .
[0056] Figure 3Figure a is a diagram showing the water contact angle effect in air on the surface of super hydrophobic flame retardant flexible materials CSM-PVA1, CSM-PVA2, CSM-PVA3, CSM-PVA4, CSM-PVA5, CSM-PVA6, CSM-PVA7, CSM-PVA8, and CSM-PVA9 prepared by mixing the precursor suspension CSM and PVA solution in different proportions. Figure 3 (b) is a diagram showing the oil contact angle effects of the surfaces of superhydrophobic flame-retardant flexible materials CSM-PVA1, CSM-PVA2, CSM-PVA3, CSM-PVA4, CSM-PVA5, CSM-PVA6, CSM-PVA7, CSM-PVA8, and CSM-PVA9 in air. Figure 4 A in the middle is a bar graph of the water contact angle in air of superhydrophobic flame-retardant flexible materials made from water-dispersible plant nanocellulose composites in different proportions. Figure 4 Figure B shows the change in the water contact angle of CSM-PVA6 superhydrophobic flame-retardant flexible material in air within 6 minutes, indicating the excellent superhydrophobic-superoleophilic properties of CSM-PVA6 superhydrophobic flame-retardant flexible material.
[0057] ②CSM-PVA6 is a scanning electron microscope (SEM) image at different magnifications.
[0058] like Figure 5 As shown in the figure, CSM-PVA6 presents a three-dimensional porous network structure in which CNF and PVA are interconnected through hydrogen bonding. This structure gives the material the advantages of high separation efficiency, flux and adsorption capacity. Figure 5 In (a) and (b), CSM-PVA6 is distributed with large and small pores interlaced to form a dense pore structure. Under 5000-30000 magnification ( Figure 5 In (c) and (d), a large number of 300nm~2μm SiO2NPs are semi-embedded on the surface of the structure through hydrogen bonding interactions between silanol and a large number of hydroxyl groups, which greatly enhances the interaction between molecules and improves the mechanical properties and structural stability of the flexible material. At the same time, a large number of 10nm~50nm hydrophobic SiO2NPs are wrapped on the surface of the structure to form a covering layer, which becomes a barrier between the subsequent condensed phase and the flame to isolate oxygen and achieve a flame retardant effect.
[0059] ③ The prepared CSM-PVA6 super-hydrophobic flame-retardant flexible material was placed in an oil-water mixture and water respectively to observe the necessary conditions for achieving oil-water separation and emulsion separation.
[0060] like Figure 6 As shown, the CSM-PVA6 super hydrophobic flame retardant flexible material is placed in an oil-water mixture (such as Figure 6 in (a)) or water (such as Figure 6 In (b), the CSM-PVA6 super-hydrophobic flame-retardant flexible material always floats on the water surface or below the oil surface of the oil layer. At the same time, due to the surface roughness and super-hydrophobicity of the CSM-PVA6 super-hydrophobic flame-retardant flexible material, a hydration layer completely isolated from water molecules appears when immersed in an aqueous solution. This shows that the CSM-PVA6 super-hydrophobic flame-retardant flexible material has the advantages of ultra-light structure, super-hydrophobicity, and super-oleophilicity, which fully meets the expected necessary conditions for oil-water separation and emulsion separation.
[0061] ④ Compare the surface and internal wettability of the CSM-PVA flexible material without heat treatment and the CSM-PVA6 super hydrophobic flame retardant flexible material prepared by heat treatment.
[0062] like Figure 7 As shown, (a) is the hydrophilic-oleophilic effect diagram of the CSM-PVA flexible material without heat treatment, (b) and (c) are the super-hydrophobic-super-oleophilic effect diagrams of the surface and the interior of the CMS-PVA6 super-hydrophobic flame-retardant flexible material after heat treatment, respectively. The CMS-PVA super-hydrophobic flame-retardant flexible material prepared by loading SiO2NPS and freeze-drying has good rough structure and mechanical properties. Secondly, the chemical modification of MTMS can generate silicon-oxygen bonds that are highly repellent to water molecules, that is, when MTMS contacts the surface of a hydroxyl-rich material, the methyl and methoxy groups in MTMS react with the hydroxyl groups on the surface of the material to form a silicon-oxygen bond covering layer, thereby making the surface and internal structure of the CMS-PVA6 super-hydrophobic flame-retardant flexible material have excellent super-hydrophobicity and corrosion resistance.
[0063] ⑤Compression rebound performance test of CSM-PVA6 super hydrophobic flame retardant flexible material under different conditions.
[0064] The mechanical properties of flexible materials are also important indicators for achieving oil-water separation. Figure 8 As shown in Figure 2, the CMS-PVA6 super hydrophobic flame retardant flexible material can achieve excellent rebound effect after multiple compressions. Fig. 9 As shown in the figure, a 200 g weight is placed on the surface of the CMS-PVA6 super hydrophobic flame retardant flexible material and remains there for 60 s, and it can still rebound well. In addition, the original height (H), radius (R), volume (V), mass (M), and density (P) of the flexible material are 14.91 mm, 10.24 mm, and 4.912 cm, respectively. 3 , 0.226 g, 0.046 g·cm -3 After the CMS-PVA6 super-hydrophobic flame-retardant flexible material was subjected to a weight static pressure test for 60 seconds, the height, radius, volume, mass, and density of the flexible material changed very slightly, which were 14.80 mm, 10.26 mm, and 4.895 cm, respectively.3 , 0.226 g, 0.0462 g·cm -3 It was calculated that the volume of the flexible material after compression for 60 s still remained at 99.65% of its original volume, while its density only increased by 0.43% compared with the original density.
[0065] like Fig.10 As shown in the figure, the cyclic stress-strain curve of CMS-PVA6 super hydrophobic flame retardant flexible material at a strain of 80% was evaluated by a universal testing machine. The maximum stress of the flexible material under 1, 5, 10, 15, 20, 25, and 30 cyclic compression and rebound tests were 88.8 kPa, 87.5 kPa, 76.5 kPa, 64.5 kPa, 60.9 kPa, 45.3 kPa, and 40 kPa, respectively. Fig.10 It can be seen that after 10 cycles of testing, the compressive strength did not decrease significantly, which means that the changes in the material structure during this stage were minimal. After 30 cycles of testing, its internal structure collapsed to a certain extent, resulting in a decrease in the overall compressive strength of the flexible material, but its appearance and structure remained good, showing good deformation recovery ability, which also provided an important basis for its application in the fields of oil-water separation and flame retardancy.
[0066] Fig.11 This is a picture showing the effect of the compression-rebound performance test of CMS-PVA6 super hydrophobic flame-retardant flexible material measured using a universal testing machine. The material can quickly recover its original structure after compression. Fig.12 As shown in the figure, after being wetted with chloroform, the CMS-PVA6 super-hydrophobic flame-retardant flexible material also has good compression resilience under 80% stress-strain conditions. This also shows that the CMS-PVA6 super-hydrophobic flame-retardant flexible material can achieve the circulation and continuous separation of oil-water mixtures through adsorption-extrusion.
[0067] (2) Tests on the oil-water separation performance of CSM-PVA6 super-hydrophobic flame-retardant flexible material and the adsorption capacity of super-hydrophobic flame-retardant flexible material for various types of light oil and heavy oil at different ratios.
[0068] ① Observe the dynamic contact angle of water under oil of CSM-PVA6 superhydrophobic flame-retardant flexible material to determine its excellent superhydrophobic and anti-pollution properties.
[0069] like Fig.13As shown, the CSM-PVA6 superhydrophobic flame retardant flexible material is placed in n-hexane, and water droplets dyed with methylene blue are continuously squeezed out of the syringe. The needle is positioned under the oil and on the upper surface of the flexible material. It can be observed that the blue droplets continuously squeezed out from the needle quickly slide down the surface of the CSM-PVA6 superhydrophobic flame retardant flexible material, indicating that the surface and interior of the CSM-PVA6 superhydrophobic flame retardant flexible material are fully covered with hydrophobic long-chain groups.
[0070] ②The stability of CSM-PVA6 super-hydrophobic flame-retardant flexible material in oil-water mixtures (n-hexane / water, chloroform / water), and its adsorption efficiency for various oils (Sudan Red III dyeing).
[0071] like Fig.14 (a) and (b) are mixtures of n-hexane / water and chloroform / water, respectively, where n-hexane and chloroform each contain 3 mL. Use tweezers to place the CSM-PVA6 super-hydrophobic flame-retardant flexible material in two different oil-water mixtures. When it first comes into contact with the mixture, the CSM-PVA6 super-hydrophobic flame-retardant flexible material shows excellent adsorption efficiency, that is, it selectively and quickly absorbs the oil in it. In 5 seconds, it can achieve complete adsorption of light oil (n-hexane) and heavy oil (chloroform), which is attributed to the rich pore structure and super-hydrophobic-super-oleophilic properties of the CSM-PVA6 super-hydrophobic flame-retardant flexible material.
[0072] ③The oil-water separation performance test was carried out by driving the CSM-PVA6 super-hydrophobic flame-retardant flexible material with a peristaltic pump.
[0073] n-Hexane, dichloroethylene, dichloromethane and chloroform were used as oil spill models of light oil and heavy oil respectively and then mixed with water to prepare oil-water mixture. Fig.15 The figure shows the oil-water separation test process of CSM-PVA6 super hydrophobic flame retardant flexible material for four oil-water mixtures. One end of the hose is connected to the CSM-PVA6 super hydrophobic flame retardant flexible material and immersed in the oil-water mixture, and the other end of the hose is placed in a beaker for oil spill repair and collection, so as to realize the continuous recovery of various oil products from oily wastewater.
[0074] Due to the super oleophilicity of the CSM-PVA6 super hydrophobic flame retardant flexible material and the pressure difference generated by the peristaltic pump, the oil in the oily wastewater is sucked into the hose from the inside of the super hydrophobic flame retardant flexible material. When the peristaltic pump is turned on, the CSM-PVA6 super hydrophobic flame retardant flexible material is placed on the water surface, and the n-hexane floating on the water surface is pumped into the beaker through the hose, and only clear water is left in the beaker originally filled with an oil-water mixture. Similarly, when the peristaltic pump is turned on, the CSM-PVA6 super hydrophobic flame retardant flexible material is placed under the water surface and brought into contact with the heavy oil at the bottom. The heavy oil at the bottom is also quickly pumped into the filter beaker, and only clear water is left in the beaker originally filled with an oil-water mixture, indicating that the CSM-PVA6 super hydrophobic flame retardant flexible material has excellent water repellency and oil-water separation effects. This once again proves the great potential of CSM-PVA6 superhydrophobic flame-retardant flexible materials in oil-water separation applications. It can simultaneously handle the collection of high-throughput oil spills and the continuous separation of oil-water mixtures, and has broad application prospects in large-scale oil spill treatment.
[0075] ④Performance test of gravity-driven CSM-PVA6 superhydrophobic flame-retardant flexible material for separating oil-water mixture.
[0076] Fig.16 The equipment in (a) is divided into three parts: the upper part is the cylinder, the middle part is the filter layer (where the CSM-PVA6 super-hydrophobic flame-retardant flexible material is placed), and the lower part is the collection bottle, which is a gravity-driven separation device. n-Hexane, dichloroethylene, dichloromethane and chloroform are used as oil spill models of light oil and heavy oil, respectively, and then mixed with water to obtain an oil-water mixture. Fig.16 (c) is a diagram of the oil spill treatment process of CSM-PVA6 super-hydrophobic flame-retardant flexible material. When the oil-water mixture is poured into the cylinder, the oil (dyed with Sudan Red III) quickly passes through the CSM-PVA6 super-hydrophobic flame-retardant flexible material in the filter layer and is collected by the collection bottle below, while the water (dyed with methylene blue) is completely blocked at the top by the super-hydrophobic flame-retardant flexible material, realizing gravity-driven recovery of various types of oil in oily wastewater. Fig.16 (b) shows the separation flux and efficiency of CSM-PVA6 super hydrophobic flame retardant flexible material for four oil-water mixtures: n-hexane / water, dichloroethane / water, dichloromethane / water, and chloroform / water. The separation flux of chloroform is 18462 L·m -2 ·h -1 The separation efficiency is 99.6%; the separation flux of dichloromethane is 15923 L·m -2 ·h -1 The separation efficiency is 99.3%; the separation flux of n-hexane is 15625 L·m -2 ·h -1 The separation efficiency is 99.2%; the separation flux of ethylene dichloride is 15873 L·m -2 ·h-1 , the separation efficiency is 99.5%.
[0077] ⑤ Gravity-driven CSM-PVA6 superhydrophobic flame-retardant flexible material separation of oil-water mixture recycling performance test.
[0078] When the chloroform / water mixture (V:V = 1:1) was poured into the filtration device, the chloroform (Sudan III dye) quickly passed through the CSM-PVA6 super-hydrophobic flame-retardant flexible material and was collected by the collection bottle below, while the water (methylene blue dye) was completely trapped on the upper part of the super-hydrophobic flame-retardant flexible material. Fig.17 As shown in the first separation test of CSM-PVA6 super hydrophobic flame retardant flexible material on chloroform / water mixture, its filtration flux for chloroform / water mixture was as high as 18462 L·m -2 ·h -1 , the separation efficiency is as high as 99.6%. In addition, at the end of each cycle, the CSM-PVA6 super-hydrophobic flame-retardant flexible material can be regenerated by squeezing and ethanol washing before the next separation test. After 12 cycles, the separation flux and efficiency of the CSM-PVA6 super-hydrophobic flame-retardant flexible material remained at 76.3% and 98.5% of the initial values, respectively, indicating that the material has good stability and reusability.
[0079] ⑥The influence of the ratio of CSM and PVA on the adsorption capacity of CSM-PVA superhydrophobic flame retardant flexible material for various light oils and heavy oils.
[0080] like Fig.18 As shown, the adsorption capacities of CSM-PVA5 super hydrophobic flame retardant flexible material for chloroform, ethylene dichloride, dichloromethane and n-hexane are 10.04 g / g, 11.25 g / g, 11.5 g / g and 4.68 g / g, respectively; the adsorption capacities of CSM-PVA6 super hydrophobic flame retardant flexible material for chloroform, ethylene dichloride, dichloromethane and n-hexane are 34.2 g / g, 27.78 g / g, 22.34 g / g and 8.14 g / g, respectively; the adsorption capacities of CSM-PVA7 super hydrophobic flame retardant flexible material for chloroform, ethylene dichloride, dichloromethane and n-hexane are 28.48 g / g, 24 g / g, 11.6 g / g and 5.23 g / g, respectively. Among them, CSM-PVA6 superhydrophobic flame-retardant flexible material has the highest adsorption capacity for various oils (chloroform, ethylene dichloride, dichloromethane and n-hexane), indicating that its three-dimensional porous structure and interconnected pores provide sufficient accommodation space for the adsorption of light oil or heavy oil.
[0081] (3) Optimization of the oil-in-water emulsion separation performance of CSM-PVA6 superhydrophobic flame-retardant flexible material.
[0082] ① Test of the separation performance of CSM-PVA6 superhydrophobic flame-retardant flexible material on various emulsions prepared with Span-80 emulsifier.
[0083] In addition to the immiscible oil-water mixture, oily wastewater also contains small droplet emulsions with stable surface activity, and the use of high-throughput separation technology to treat emulsions and emulsions faces major challenges. Four different types of emulsions (dichloromethane / water, chloroform / water, dichloroethane / water, and hexane / water) treated with Span-80 emulsifier have excellent stability. Fig.19 The equipment is divided into three parts: the upper part is the cylinder, the middle part is the filter layer (where CSM-PVA6 super-hydrophobic flame-retardant flexible material is placed), and the lower part is the collection bottle, which is a gravity-driven separation device. Fig. 20 The following is a comparison of the effects of four different types of emulsions before and after separation. Fig.21 As shown in Figure 2, the separation flux of dichloromethane / water emulsion is 5000 L·m -2 ·h -1 The separation efficiency is 99.6%; the separation flux of chloroform / water emulsion is 10000 L·m -2 ·h -1 , the separation efficiency is 99.5%; the separation flux of dichloroethane / water emulsion is 13333 L·m -2 ·h -1 The separation efficiency is 99.4%; the separation flux of n-hexane / water emulsion is 10526 L·m -2 ·h -1 , the separation efficiency is 99.1%. The test results show that the separated solution is clear and transparent, indicating that the CSM-PVA6 super-hydrophobic flame-retardant flexible material has significant separation performance for oil-water emulsions.
[0084] ②Test on the cyclic separation performance of CSM-PVA6 super hydrophobic flame retardant flexible material for various emulsions.
[0085] like Fig. 22 As shown in the figure, taking ethylene dichloride / water emulsion as an example, the CSM-PVA6 superhydrophobic flame-retardant flexible material was subjected to 10 oil-water separation cycle tests. In the first cycle test, the separation flux of ethylene dichloride / water emulsion was as high as 13333 L·m -2 ·h -1, the separation efficiency is as high as 99.4%, which confirms the efficient separation effect of the super hydrophobic flame retardant flexible material on oil-water mixture. In addition, after each test, the CSM-PVA6 super hydrophobic flame retardant flexible material can be regenerated by squeezing and ethanol washing, and then the next separation test is carried out. After 10 cycles, the separation flux and efficiency of the CSM-PVA6 super hydrophobic flame retardant flexible material remained at 80.2% and 98.8% of the initial value, respectively, indicating that the material has good stability and reusability.
[0086] (2) Flame retardant properties and adsorption-combustion-desorption cycle performance test of CSM-PVA6 super hydrophobic flame retardant flexible material.
[0087] ① Flame retardant performance test of CSM-PVA6 super hydrophobic flame retardant flexible material in air.
[0088] like Fig.23 As shown in the figure, the CSM-PVA6 super hydrophobic flame retardant flexible material completely exposed to air continued to burn for 6 seconds in the combustion test and extinguished itself within only 2 seconds, showing excellent flame retardant and fireproof properties. This is because the SiO2NPS and hierarchical porous structure loaded inside the CSM-PVA6 super hydrophobic flame retardant flexible material significantly enhance its flame retardancy, making it a promising ultra-light fire-resistant material.
[0089] ② Flame retardant performance test of CSM-PVA6 super hydrophobic flame retardant flexible material in air after oil absorption.
[0090] Fig.24 (a) is a comparison of the CSM-PVA6 super hydrophobic flame retardant flexible material before and after combustion in a state of saturated n-hexane adsorption. Since a large amount of flammable n-hexane is adsorbed inside the structure and it is completely exposed to the air, the axial structure of the CSM-PVA6 super hydrophobic flame retardant flexible material collapses slightly and carbonizes more seriously after combustion. The CSM-PVA6 super hydrophobic flame retardant flexible material in a state of saturated n-hexane adsorption is squeezed to remove most of the flammable n-hexane in its internal structure. The comparison of the effects before and after combustion is shown in the figure below. Fig.24 As shown in (b). Since the CSM-PVA6 super hydrophobic flame retardant flexible material has been extruded, its internal structure contains only a small amount of residual flammable oil. Therefore, although it is completely exposed to the air, at the end of the combustion, the overall structure of the CSM-PVA6 super hydrophobic flame retardant flexible material has hardly collapsed, and only carbonization occurs on its surface.
[0091] ③ Flame retardant performance test of CSM-PVA6 super hydrophobic flame retardant flexible material after oil absorption when it is isolated from most of the air.
[0092] like Fig.25As shown, CSM-PVA6 super hydrophobic flame retardant flexible material is placed in a small glass bottle, and is fixed upside down with an iron stand to make a simple combustion test device that isolates most of the air. When burning to 60s, most of the oil in the structure of CSM-PVA6 super hydrophobic flame retardant flexible material has been burned and removed. When burning to 120s, the oil in the internal structure of CSM-PVA6 super hydrophobic flame retardant flexible material is further removed by burning. When burning to 160s, the residual oil in the CSM-PVA6 super hydrophobic flame retardant flexible material is completely removed by burning. After the burning is completed, the overall structure and morphology of CSM-PVA6 super hydrophobic flame retardant flexible material have hardly changed, indicating its excellent cyclic adsorption-combustion desorption performance and flame retardant properties.
[0093] ④Study on the high adsorption performance, adsorption-desorption combustion cycle performance and rapid combustion regeneration process of CSM-PVA6 superhydrophobic flame retardant flexible material.
[0094] Fig.26 The performance test results of 10 adsorption-combustion-desorption cycles of n-hexane on CSM-PVA6 super hydrophobic flame retardant flexible material. The n-hexane adsorbed inside the CSM-PVA6 super hydrophobic flame retardant flexible material can be completely removed by combustion without destroying its overall structure. The first adsorption capacity and mass of n-hexane on CSM-PVA6 super hydrophobic flame retardant flexible material are 8.69 g / g and 0.055 g / cm -3 Even after 10 consecutive adsorption-combustion-desorption cycle tests, the oil absorption of the CSM-PVA6 super-hydrophobic flame-retardant flexible material remained at 90.5% of the original oil absorption, and its dead weight remained at 94.1% of the original mass.
[0095] Fig. 27 The following are photos of the CSM-PVA6 super-hydrophobic flame-retardant flexible material before and after 10 adsorption-combustion-desorption cycle tests. Although its surface morphology and radial microstructure have slightly blackened and shrunk, after multiple adsorption-combustion-desorption cycle tests, it still retains its original structural stability and oil absorption capacity, demonstrating the excellent recyclability of the CSM-PVA6 super-hydrophobic flame-retardant flexible material. With its superior oil absorption capacity and recovery stability, the CSM-PVA6 super-hydrophobic flame-retardant flexible material has become an ideal choice for oil removal in practical applications, especially in the field of offshore oil spills.
[0096] (3) Test on the strong acid, strong alkali and salt resistance of CSM-PVA6 super hydrophobic flame retardant flexible material.
[0097] In order to adapt to complex environments, chemical durability is an important indicator for evaluating the universality of CSM-PVA6 super hydrophobic flame retardant flexible materials. Sodium hydroxide and concentrated sulfuric acid solutions were used to simulate various extreme environments from strong alkali to strong acid. Fig.28 As shown in the figure, when the CSM-PVA6 superhydrophobic flame-retardant flexible material is placed in a strong acid environment with a pH value of 1 to 7, its surface water contact angle is always stable at more than 150°; when the CSM-PVA6 superhydrophobic flame-retardant flexible material is placed in a strong base environment with a pH value of 8 to 12, its surface water contact angle is also always stable at 150°. Since the Si-OC group is more easily hydrolyzed in a strong base than in a strong acid, the acid resistance of the CSM-PVA6 superhydrophobic flame-retardant flexible material is better than its alkali resistance. In addition, we also cut the CMS-PVA6 superhydrophobic flame-retardant flexible material into pieces to study the structural stability and tolerance of its surface and internal structure in the extreme environments of strong acid, strong base and salt. After 168 h of immersion in a strong acid solution of pH=1, a strong base solution of pH=14 and a 5 wt% salt solution, the CMS-PVA6 superhydrophobic flame-retardant flexible material still maintained excellent structural stability, demonstrating its tolerance to strong acid, strong base and high-concentration salt solutions. Therefore, CSM-PVA6 super-hydrophobic flame-retardant flexible material can achieve good oil / organic solvent adsorption effect under various harsh conditions, and its good reusability and chemical stability make CSM-PVA6 super-hydrophobic flame-retardant flexible material have broad application prospects in marine oil spill incidents.
[0098] The present invention sequentially blends silicon dioxide nanoparticles (SiO2NPS), methyltrimethoxysilane (MTMS) and nanocellulose (CNF) suspension to complete the reaction, and then blends with a low concentration of polyvinyl alcohol (PVA) solution to obtain a water-dispersible plant nanocellulose complex, and further freeze-dries to prepare a super-hydrophobic flame-retardant flexible material with a three-dimensional super-porous structure. Among them, SiO2NPS is attached to the surface of nanocellulose, simulating a large number of nano-scale rod-like structures attached to the convex structure of the lotus leaf surface, while changing the rough structure of the material surface, enhancing its structural stability and giving it flame-retardant properties; MTMS is used to modify the surface and interior of the material by grafting silane long chains to achieve a low surface energy hydrophobic effect similar to the lotus leaf surface; the introduction of PVA solution for blending can give the material better flexibility.
[0099] The present invention uses water to replace organic solvent as a water dispersion system of the dispersion medium to realize the preparation of a porous super-hydrophobic flame-retardant flexible material from a water-dispersible plant nanocellulose composite. The material preparation process is green and pollution-free, and the safety hazards such as air pollution and fire caused by the volatilization of organic solvents are better avoided, and the material has the characteristics of high elasticity, high oil absorption, reusability, fire resistance, and degradability. The present invention can effectively reduce the production cost of the material and good flame retardancy. Not only has it broadened the application field of the material, but it has also improved its safety, cycle stability and reusability in oil-water separation applications. The flexible material prepared by the present invention can not only achieve its rapid and highly selective separation by various methods such as adsorption, filtration, and suction filtration when separating oil-water mixed liquids, emulsions, etc., but also can be used as a recyclable organic liquid fuel carrier, and the internal oil pollution of the material after burning is completely removed, and it still has excellent super-hydrophobicity, high oil absorption, flame retardancy and flexibility, showing excellent reusability.
[0100] Therefore, the present invention adopts the method for preparing super-hydrophobic flame-retardant flexible materials using the above-mentioned water-dispersible nanocellulose composites. The material preparation process is green and pollution-free, and the prepared flexible material has the characteristics of high elasticity, high oil absorption, reusability, fire resistance, degradability, etc., and can be applied to various fields.
[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a super-hydrophobic flame-retardant flexible material by using a water-dispersible nanocellulose composite, characterized in that: The following steps are involved: Step 1, nanocellulose CNF suspension; Step 2, synthesizing silicon dioxide nanoparticles SiO2 NPS; Step 3, preparing a precursor suspension CSM: mixing SiO2 nanoparticles, methyltrimethoxysilane MTMS and nanocellulose suspension in proportion, reacting to obtain a precursor suspension CSM; Step 4, preparing a polyvinyl alcohol (PVA) solution: adding PVA solid to deionized water, heating and stirring at 85° C. until completely dissolved, to obtain a PVA solution; Step 5, preparing a water-dispersible plant nanocellulose composite CSM-PVA mixed solution: blending the materials prepared in step 3 and step 4 to prepare a CSM-PVA mixed solution, and freezing the mixture; Step 6, freeze-drying the frozen material, and then placing it in an oven for heat treatment to obtain a super hydrophobic flame retardant flexible material.
2. The method for preparing a super-hydrophobic flame-retardant flexible material from a water-dispersible nanocellulose composite according to claim 1, characterized in that: The preparation method of the nanocellulose CNF suspension in step 1 is: the straw raw material is prepared by hot solvent pretreatment, low eutectic solvent separation, sodium chlorite solution bleaching, and high-intensity ultrasonic treatment; the concentration of the nanocellulose CNF suspension is 0.95~1.05 wt%.
3. The method for preparing a super-hydrophobic flame-retardant flexible material from a water-dispersible nanocellulose composite according to claim 1, characterized in that: The specific operation of step 2 is: mixing anhydrous ethanol, deionized water and ammonia water, and preparing liquid A after ultrasonic treatment; mixing tetraethyl orthosilicate TEOS and anhydrous ethanol, and preparing liquid B after ultrasonic treatment; at 45°C, slowly pouring liquid A into liquid B twice in a ratio of 3 / 4 and 1 / 4, every 1 hour, after the reaction is completed, centrifuging in a centrifuge, rinsing with deionized water and ethanol, and drying to obtain SiO2 nanoparticles.
4. The method for preparing a super-hydrophobic flame-retardant flexible material from a water-dispersible nanocellulose composite according to claim 1, characterized in that: In step 3, the mass ratio of nanocellulose suspension: SiO2 nanoparticles: methyltrimethoxysilane is 3.70~3.80 g: 0.025~0.031 g: 0.9~1.1 g.
5. The method for preparing a super-hydrophobic flame-retardant flexible material from a water-dispersible nanocellulose composite according to claim 1, characterized in that: The concentration of the PVA solution in step 4 is 9.5-10.5 mg / mL.
6. The method for preparing a super-hydrophobic flame-retardant flexible material from a water-dispersible nanocellulose composite according to claim 1, characterized in that: The specific operation of step 5 is: the precursor suspension CSM and the PVA solution are mixed and reacted according to the proportion, and after mechanical stirring at a speed of 1950-2050 rpm for 4-6 minutes, a water-dispersible plant nanocellulose composite CSM-PVA mixed solution is obtained.
7. The method for preparing a super-hydrophobic flame-retardant flexible material from a water-dispersible nanocellulose composite according to claim 6, characterized in that: The dosage ratio of the precursor suspension CSM and the PVA solution is (1-5): (1-5).
8. A super hydrophobic flame retardant flexible material prepared by the method according to any one of claims 1 to 7.
9. Use of the super hydrophobic flame retardant flexible material as claimed in claim 8 in separation of oily wastewater and emulsion.
10. Use of the super hydrophobic flame retardant flexible material according to claim 8 in flame retardancy, circulating oil adsorption, and combustion desorption.
Citation Information
Patent Citations
Composite super-hydrophobic particle, preparation method thereof and super-hydrophobic coating preparation method
CN105237811A
Fireproof and flame-retardant straw composite material as well as preparation method and application thereof
CN112852447A
Preparation method of oriented nanocellulose montmorillonite aerogel
CN114479197A
Preparation method of nano cellulose / polyvinyl alcohol / nano silicon dioxide composite film
CN117510920A
Method for separating furfural residue lignin by using gas-phase eutectic solvent method
CN118477345A
Cited By
Photoelectric thermomagnetic control biomass composite material with simple wettability switching prepared by water-phase one-pot method and application of photoelectric thermomagnetic control biomass composite material
CN120695797A
Preparation and Application of Photoelectric, Thermomagnetic, and Biomass Composite Materials with Easily Switchable Wettability Using a One-Pot Aqueous Method
CN120695797B
